Plastics occurrence in the gastrointestinal tract of Zeus faber and Lepidopus caudatus from the Tyrrhenian Sea. (September 2019) - Bottari, Teresa; Savoca, Serena; Mancuso, Monique; Capillo, Gioele; GiuseppePanarello, Giuseppe; MartinaBonsignore, Martina; Crupi, Rosalia; Sanfilippo, Marilena; D'Urso, Luisa; Compagnini, Giuseppe; Neri, Fortunato; Romeo, Teresa; et al.
Abstract: The present study investigates the occurrence of plastic pollution in two commercially important marine teleosts ( Zeus faber and Lepidopus caudatus ) from the northern coasts of Sicily (Tyrrhenian Sea). Plastics occurrence in the gastrointestinal tract was higher in Lepidopus caudatus (78.1%) than Zeus faber (51.4%). Debris characterization, carried out by micro-Raman spectroscopy, allowed identified the main types of found polymers as: polypropylene (PP), polyamide (PA), nylon and, to a lesser extent, polyethylene (PE). Of the two fish species studied, the silver scabbardfish appeared to be the more vulnerable to plastic ingestion. Our study represents a starting point that may pave the way for future investigation of the fate, accumulation and transfer of plastic debris to upper trophic levels, to verify their potential toxicity and to better understand strategies to mitigate this phenomenon. Graphical abstract: Unlabelled Image Highlights: Meso and microplastics were found in gastrointestinal tract of Z. faber and L. caudatus from Tyrrhenian Sea. The most of plastics (99.1%) appeared in fibers shapes. μ-Raman spectroscopy characterized plastics as PE, Nylon, PA, PP and acrylic fibers.